2007
DOI: 10.1177/147323000703500517
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Glycation End Products Inhibit Production and Activity of Matrix Metalloproteinase-2 in Human Umbilical Vein Endothelial Cells

Abstract: The aim of this study was to investigate the effects of advanced glycation end products

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…23 In contrast, earlier study suggested that the stimulation of AGE receptors resulted in upregulation of inflammatory cytokines and MMPs, contributing to aneurysmal formation. 37,38 In support of this, a recent study found that serum concentrations of the AGE carboxymethyllysine were lower in patients with AAA. 39 Glycation of the aortic media inhibits MMP secretion (in contrast to glycation of atherosclerotic intima which stimulates MMP secretion 23,30 ).…”
Section: Biology Of the Wallmentioning
confidence: 82%
“…23 In contrast, earlier study suggested that the stimulation of AGE receptors resulted in upregulation of inflammatory cytokines and MMPs, contributing to aneurysmal formation. 37,38 In support of this, a recent study found that serum concentrations of the AGE carboxymethyllysine were lower in patients with AAA. 39 Glycation of the aortic media inhibits MMP secretion (in contrast to glycation of atherosclerotic intima which stimulates MMP secretion 23,30 ).…”
Section: Biology Of the Wallmentioning
confidence: 82%
“…Hence, a situation where post-translational modifications on collagen, e.g. glycation, that effectively inhibit proteolysis by MMPs, could ultimately result in decreased collagen degradation even if MMPs activity was increased 49 .…”
Section: Discussionmentioning
confidence: 99%
“…21,26 Furthermore, AGEs enable covalent cross-linking, which promotes the stiffening of the ECM, rendering it less prone to proteolysis, and decreasing the possibility of aneurysmal growth and rupture. 20,21,27,28 Additionally, patients with type 2 DM have 2-fold reduced levels and activity of MMP-2 and MMP-9, thus restricting the degradation and remodeling of aortic wall ECM proteins. 21,29 Moreover, EMMPRIN (membrane-bound protein inducing expression of several MMPs) levels in the arterial tissue are decreased in DM, indicating that reduced inducer protein levels may result in decreased MMP expression.…”
Section: Discussionmentioning
confidence: 99%